EFEKTIVITAS MEDIA PEMBELAJARAN DAKOTA (DAKON MATEMATIKA) DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA DI SEKOLAH DASAR - Sugiyanta, Geyol; Trisnani, Novy; Santika, Yessy (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
This study aims to find out whether the use of Dakota or Dakon Matematika learning media is effective in improving students' Mathematics learning outcomes in elementary schools, especially in learning materials for Least Common Multiple (KPK) and Greatest Common Factor (FPB). This study uses a library research methodology (library research). The study materials in this study used 8 main books, 13 main research articles and 7 previous studies, as materials or sources in this research. Analysis using description. The results of the study stated that Dakota or Dakon Matematika learning media is a visual learning media that is effective in improving student learning outcomes in elementary schools on KPK and FPB material. In addition, the use of Dakota learning media makes the learning process in class more effective, fun, and increases student activity in learning.